A PRELIMINARY NOTE ON THE BLACK SNOEK, Thyrsitoides marleyi Fowler, 1929 (PISCES: GEMPYLIDAE) FROM INDIAN WATERS - AMBARISH P. GOP, S. SURYA N. S. JEENA, N. K. MIDHUNRAJ; PRATHIBHA ROHIT, K. K. SURESH, M. K. ANIL, . BSANTHOSH, E. M. ABDUSAMAD AND (The Bioscan, 2018)
Thyrsitoides marleyi Fowler, 1929 (Black snoek, Black sail snake mackerel), a monotypic species of the genus Thyrsitoides under the family Gempylidae was collected from the hook and line fishers of the south west coast of India to study the morphometrics, meristics and molecular credentials of the fish. The morphometrics, meritics and the DNA barcode of the fish emphasises the monotypic nature of the fish family. The DNA barcode (Accession no.: MG886840), upon comparison with NCBI database, confirmed that the species was Thyrsitoides marleyi, which exhibited an identity of 99% to T.marleyi from Japanese waters (Accession: AP012505.1). The X ray photograph of the fish depicted the presence of two rows of intramuscular bones stretching from the dorsal and ventral side of the vertebral column on both sides forms one of the major distinguishing characteristics of the fish. The study pertinent to different facet cleared the taxonomic ambiguity of T.marleyi with T.jordanus, another species yet to be described